Use of IFN-Based Biotherapeutics to Harness the Host Against Foot-And-Mouth Disease - Medina, Gisselle N.; de los Santos, Teresa; Diaz-San Segundo, Fayna (Frontiers in Veterinary Science, 2020)
Foot-and-Mouth Disease (FMD) is a highly contagious vesicular disease of cloven-hoofed animals that severely constrains international trade of livestock and animal products. Currently, disease control measures include broad surveillance, enforcement of sanitary policy, and use of an inactivated vaccine. While use of these measures has contributed to eliminating FMDV from a vast area of the world, the disease remains endemic in three continents, and outbreaks occasionally appear in previously declared FMD-free zones, causing economic and social devastation. Among others, a very fast rate of viral replication and the need of 7 days to achieve vaccine-induced protection are the main limitations in controlling the disease. New fast acting antiviral strategies targeted to boost the innate immunity of the host to block viral replication are needed. Here we review the knowledge on the multiple strategies FMDV has evolved to block the host innate immunity, with particularly focus on the past and current research towards the development of IFN-based biotherapeutics in relevant livestock species.